Predicting Predator Nutrient Intake From Prey Body Contents - Wilder, Shawn M.; Barnes, Cody L.; Hawlena, Dror (Frontiers in Ecology and Evolution, 2019)
Predator-prey interactions can have important consequences for the flow of nutrients through food webs and ecosystems. Given the diversity of predator-prey interactions, it is infeasible to directly measure predator nutrient intake when feeding on each potential prey. Elements are an important measure of nutrient flow through food webs but do not fully account for variation in the quality of nutrients in which they are present. The overall goal of this study was to test if measures of macronutrients, metabolizable protein and lipid, could be used to improve measures of elemental ingestion by predators when feeding on prey. This experiment used two prey that differed widely in exoskeleton content (i.e., larval vs. adult mealworms) because arthropod prey vary widely in this trait and it has the potential to complicate nutritional measurements since it contains nitrogen but is indigestible to most predators. Our results show that the elemental content of whole prey was a poor predictor of elemental consumption by predators. Macronutrient content of whole prey was a strong predictor of macronutrient ingestion by predators, which suggested that it may be a useful measure of predator consumption. Using macronutrient data to create a hybrid element-macronutrient measure of whole prey resulted in better predictions of total elemental ingestion by predators. These results suggest that combining elemental and macronutrient approaches in the study of trophic transfers of nutrients, especially during predator-prey interactions, has the potential to increase our ability to understand and predict the flow of nutrients through food webs and ecosystems.